2018
DOI: 10.1155/2018/2142519
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Inpatient Mortality in Elderly People with Acute Kidney Injury

Abstract: Background Acute Kidney Injury (AKI) is common in elderly people (EP). There is paucity of data on predictor of mortality in EP with AKI. Objective This study was done to know more about factors associated with inpatient mortality in EP with AKI. Methods We retrospectively reviewed medical records of patients aged 65 years or above hospitalized with a diagnosis of AKI at Aga Khan University Hospital, Karachi, between January 2005 and December 2010. Binary logistic regression models were constructed to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…According to previous studies, worse baseline renal function and more frequent intradialytic hypotension were associated with lower likelihood of renal recovery 31,32 . Presence of stage III AKI, oliguria, and hemodynamic instability needing vasopressor are associated with increased mortality 33 . Increased median bicarbonate, presence of hypertension, and high admission creatinine were various factors associated with decreased inpatient mortality 33 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…According to previous studies, worse baseline renal function and more frequent intradialytic hypotension were associated with lower likelihood of renal recovery 31,32 . Presence of stage III AKI, oliguria, and hemodynamic instability needing vasopressor are associated with increased mortality 33 . Increased median bicarbonate, presence of hypertension, and high admission creatinine were various factors associated with decreased inpatient mortality 33 .…”
Section: Discussionmentioning
confidence: 94%
“…Increased median bicarbonate, presence of hypertension, and high admission creatinine were various factors associated with decreased inpatient mortality 33 . However, mortalities are not influenced by ages 33 . In addition, hypotension during dialysis is a serious problem and it is an independent risk factor of mortality in dialyzed patients 34,35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, some studies have reported that age was not an independent risk factor for mortality in AKI patients >60 years of age [8,27]. e mortality rate of elderly patients with AKI has been reported to be 18%-61% [8,[28][29][30]; this wide range could be due to the heterogeneity of the study populations, availability of a critical care unit, standard of care administered, or research methodology used. e present study reported similar in-hospital mortality rates between the elderly and nonelderly patients with AKI.…”
Section: Discussionmentioning
confidence: 99%